Pemanfaatan Etnomatematika Untuk Meningkatkan Aktivitas Dan Hasil Belajar Siswa Kelas IV SDN 1 Senggrong - oktavia nurhana zulfa; Anggit Grahito Wicaksono; Ema Butsi Prihastari (Journal on Education, 2023)
This research was conducted at SD Negeri 1 Senggrong Boyolali. The subjects in this study were grade IV students. This research is included in Classroom Action Research (PTK) which is carried out in two cycles, each cycle consisting of 4 meetings. Interviews, observation, documentation are the techniques used in data collection. After all the data has been collected, the researcher processes the data using a comparative descriptive analysis technique. Ethnomathematics is proven to be able to increase the activity and learning outcomes of mathematics, it can be seen from the pre-cycle data that only 40% achieve a score of 75 as the Minimum Completeness Criteria (KKM). After the implementation of cycle 1, students who passed the KKM were 60% and the implementation of cycle 2 succeeded in increasing the percentage of student completeness to 80%. Referring to the results obtained, it can be concluded that at SD Negeri 1 Senggrong Boyolali Semester II for the 2021/2022 school year, the use of ethnomathematics-based picture card teaching materials is proven to be able to increase the activity and learning outcomes of class IV students.